A challenge most bigly: academic archives and higher education in the Trump Era. Issue 1 (10th January 2020) - Wiles, Bradley
Abstract : Purpose: This paper aims to provide a critical perspective on emergent issues in the Trump era directly or indirectly relevant to academic archives. It describes current operational characteristics and trends in academic archives and considers the implications of the "Trump Effect" on academic archives in support of higher education. Design/methodology/approach: The author examines archival studies literature pertaining to academic archives in combination with recent research and reporting on Trump Administration higher education policy to argue for increased professional awareness and vigilance. Findings: The author asserts that Trump Administration rhetoric and policies aimed at remaking American higher education and undermining democratic norms pose a threat to academic archives as institutions that support learning, memory and historical accountability. Originality/value: This paper adds to scholarly discussions in the library and information studies and archival studies fields about the merits of neutrality, the legacy of memory institutions and the obligation of information professionals to take a stance on difficult issues. Additionally, there are few (if any) sources that discuss the role of academic archives specifically in the contemporary political context.